The Spruce Budworm Genome: Reconstructing the Evolutionary History of Antifreeze Proteins. (7th June 2022) - Béliveau, Catherine; Gagné, Patrick; Picq, Sandrine; Vernygora, Oksana; Keeling, Christopher I; Pinkney, Kristine; Doucet, Daniel; Wen, Fayuan; Spencer Johnston, J; Maaroufi, Halim; Boyle, Brian; Laroche, Jérôme; et al.
Abstract: Insects have developed various adaptations to survive harsh winter conditions. Among freeze-intolerant species, some produce "antifreeze proteins" (AFPs) that bind to nascent ice crystals and inhibit further ice growth. Such is the case of the spruce budworm, Choristoneura fumiferana (Lepidoptera: Tortricidae), a destructive North American conifer pest that can withstand temperatures below −30°C. Despite the potential importance of AFPs in the adaptive diversification of Choristoneura, genomic tools to explore their origins have until now been limited. Here, we present a chromosome-scale genome assembly for C. fumiferana, which we used to conduct comparative genomic analyses aimed at reconstructing the evolutionary history of tortricid AFPs. The budworm genome features 16 genes homologous to previously reported C. fumiferana AFPs (CfAFPs), 15 of which map to a single region on chromosome 18. Fourteen of these were also detected in five congeneric species, indicating Choristoneura AFP diversification occurred before the speciation event that led to C. fumiferana . Although budworm AFPs were previously considered unique to the genus Choristoneura, a search for homologs targeting recently sequenced tortricid genomes identified seven CfAFP-like genes in the distantly related Notocelia uddmanniana . High structural similarity between Notocelia and Choristoneura AFPs suggests a common origin, despite the absence of homologs in three related tortricids. Interestingly, one Notocelia AFP formed the C-terminus of a "zonadhesin-like" protein, possibly representing the ancestral condition from which tortricid AFPs evolved. Future work should clarify the evolutionary path of AFPs between Notocelia and Choristoneura and assess the role of the "zonadhesin-like" protein as precursor of tortricid AFPs.